Improving Public Speaking Skills Through the Khitobah Subject: A Case Study at Madrasah Hidayatullah Tanjung Morawa - Syari, Isma Aulia Zamaakh; Azhari, Muhammad (Electronic Journal of Education, Social Economics and Technology, 2025)
Public speaking is a critical skill for students, particularly in Islamic educational institutions where delivering religious speeches is essential. At MAS Hidayatullah Tanjung Morawa, the khitobah subject plays a central role in fostering these skills among female students (santriwati). This study aims to analyze the implementation of the khitobah subject in enhancing the public speaking abilities of santriwati. Using a descriptive qualitative approach, data were gathered through observation, interviews, and documentation as primary sources, complemented by books and relevant articles as secondary references. The data were analyzed through processes of reduction, presentation, and conclusion drawing. The findings indicate that (1) the khitobah subject extends beyond sermon delivery to include comprehensive public speaking training; (2) students' public speaking abilities vary by grade level, largely due to differences in learning experiences; and (3) the subject has shown notable effectiveness, especially in Grade XII, in boosting students' confidence, fluency, and minimizing regional accents. Regular weekly sessions and hands-on practice are key factors in improving the students' overall public speaking competence.